Hygiene and Sanitation of Fresh Cow Milk Quality in Getasanyar, Sidorejo, Magetan - Wanda Kharismatulfaiza; Djoko Windu P. Irawan; Karno Karno; Denok Indraswati; Aries Prasetyo (Health Notions, 2022)
Milk is a source of animal protein which is necessary for the growth of the human body. Fresh milk from healthy cows is obtained by using the milking method. This study aims to determine the hygiene of cage sanitation and equipment sanitation, milking behavior, and quality of fresh cow's milk in Getasanyar Village, Sidorejo District, Magetan Regency. This research is descriptive. Sampling technique with purposive sampling design. Collecting data using observation and interviews laboratory examination. The results showed that the sanitation of cattle pens for farms 1 and 2 (40%) was good (60%) bad, and farm 3 (75%) was good (25%) bad. Sanitation of farm equipment 1 and 2 (60%) good (40%) bad, farm 3 (75%) good (25%) bad. The behavior of dairy farms 1 and 2 has bad behavior, farm 3 has good behavior. The physical quality of milk does not change. The chemical quality pH and temperature of fresh cow's milk 1, 2, and 3 did not meet the requirements. The microbiological quality of the germ numbers of fresh cow's milk on farms 1, 2, and 3 met the requirements, and Escherichia coli in fresh cow's milk on farms 1 and 2 did not meet the requirements, farm 3 met the requirements. Sanitary hygiene with milking behavior on milk quality does not meet the requirements. Keywords: fresh cow milk; hygiene; sanitation; quality